Paths for improving non-profit impact on society: lessons from government–non-profit relationships in Brazil. Issue 3 (3rd April 2019) - Marchesini da Costa, Marcelo
ABSTRACT: How can non-profit organisations achieve their intended impact on society? This article analyses factors that influence non-profit action in two key situations: when these organisations work autonomously from the government, and when they work in collaboration with the government. Based on interviews with experienced non-profit leaders in Brazil, the article presents typical paths for success and common reasons for failure in achieving non-profits' intended outcomes. Organisational, relational and contextual factors influence non-profit action, leading to different outcomes. Brazilian non-profits provide lessons for non-profit action in developing countries contexts that experience cycles of political and economic instability.